Transformative Learning In Clinical Reasoning: A Meta-synthesis In Undergraduate Primary Care Medical Education - Nur Faraheen Abdul Rahman; Nathan Davies; Julia Suhaimi; Faridah Idris; Sharifah Najwa Syed Mohamad; Sophie Park (Taylor & Francis, 2024)
Indexed by WOS/Scopus